Stakeholder outreach on process safety for process industry using risk based approaches - Fauzi Rahman Jayaraman, S.N.B. (John Wiley and Sons Inc., 2020)
For past decades, the industry and academician realized the core of effective process safety management (PSM) is closely related to good process safety culture. Major accidents in process industry occur at low frequency but the consequences on people, environmental, and assets damage are catastrophic. Previous accidents in process industry recorded many deaths and injuries of facility personnel and public. Hence, many regulations and best practices were introduced to avoid major accidents from occurring and to mitigate the consequences. Risk based process safety (RBPS) Guideline is one of best practices to manage PSM, using risk-based approaches. When accidents happened, internal and external stakeholders are greatly impacted if it is not mitigated effectively. Thus, element stakeholder outreach which lies in Commit to Process Safety pillars are considered as important elements to protect the stakeholders and promoting good safety culture. This article presents a structured technique for stakeholder outreach using RBPS approaches and a work-aid model to ease its implementation in process industry. The technique and work-aid model are beneficial to help the organization managing stakeholders, educating the public on risk management and the importance of embracing safety culture in their life. Â© 2019 The Authors. Process Safety Progress published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers.